Merespon Argumentasi Ulama Al-Azhar Tentang Riba, Bunga Bank dan Kredit - Ismiati; Fansuri, Fuad (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2022)
Community life in the economic field is growing, so that new forms of economic transactions are also growing, this is inseparable from the review of Islamic law. Therefore, the discussion of usury issues will always be actual, because it is directly related to people's lives. Banks that run interest-based operations are often associated with usury issues. However, when bank interest is associated with usury, this raises controversy and raises the question of whether bank interest is the same as usury. There are two groups that address this, first the neo revivalism group which states that bank interest is usury. Second, the modernist group that says bank interest is different from usury. In this problem still contains a question, what is actually meant by the Qur'an with usury that is forbidden. To get information about this problem, the author tries to discuss it in a scientific work with the title reviewing the statement of the views of al-Azhar scholars about usury, bank interest and credit.